Growth, yıeld and yıeld attrıbutes of mustard varıetıes as ınfluenced by dıfferent growıng condıtıons (Bangladesh Journal of Botany, 2025)
As a step towards the profitable employment of nanoparticles in agriculture, effects of chitosan on mustard under water deficit stress (WDS) condition was investigated. Three growing conditions viz., well water(WW), water deficit stress and foliar application of chitosan under WDS and three mustard varieties were considered in the experiment. Water deficit stress had negative effect on morpho-physiology and yield traits of mustard. However, the ameliorative effects of chitosan application were revealed by significant improvement in those traits. BARI Sharisha-15 produced the highest seed yield ha-1 (1.59, 1.39 and 1.55 ton, respectively) under WW, WDS and chitosan treated conditions. Based on overall responses, BARI Sharisha-14 may be considered as drought tolerant and Tori-7 as drought susceptible. Foliar application of chitosan can mitigate the harmful effects of WDS on morpho-physiology and yield of mustard.Bangladesh J. Bot. 54(3): 555-562, 2025 (September)